Organized colorectal cancer screening in Serbia – The first round within 2013–2014 - Banković Lazarević, Dušica S.; Krivokapić, Zoran; Barišić, Goran; Jovanović, Verica; Ilić, Dragan; Veljković, Marko (Vojnosanitetski pregled, 2017)
Background/Aim. The National Organized Colorectal Cancer Screening Program was conducted in the Republic of Serbia during 2013–2014 covering the population of both genders, aged 50 to 74 years, in 28 municipalities out of 180, with the target population of 651,445 people. This organized colorectal cancer screening aim is to reduce mortality from colorectal cancer in the target population. The aim of this study was to show the results of organized screening for colorectal cancer during the first biannual round in Serbia. Methods. General practitioners from the primary health centers, invited target population by mail and by phone to perform immunochemical fecal occult blood test. Persons with a positive test results were referred to the colonoscopy. The database of health insurance and other citizens of the target population was used for invitation for screening in primary health centers. Descriptive statistical analysis of the results in organized colorectal cancer screening in the first round was performed for the key screening indicators. Results. In the first round a total of 99,592 persons were invited. The participation rate was 62.5%. Colonoscopy was performed in 1,554 persons. Adenomas were found in 586 persons (0.9% of all the tested), e.g. 37.7 % of all colonoscopied. In 129 persons colorectal cancer was diagnosed (0.2% of all the tested), e.g. 8.3% of all the colonoscopied. In the left half of the colon (rectum, sigmoid and descending colon) there were 70.4% diagnosed polyps and 77.3% carcinomas, while 29.6% of polyps and 22.7% carcinomas were found in the proximal parts of the colon. Conclusion. In the first round of the organized colorectal cancer screening in Serbia the participation rate of the targeted population was high and gave encouraging result. It was expected that in the forthcoming rounds even higher coverage of the target population would be accomplished. A positive predictive value of the completed colonoscopies showed that further observing the stages of diagnosed adenomas and carcinomas would reach the goals of the expected improvement in early detection of colorectal cancer in Serbia.